Targets and Mechanisms of Photodynamic Therapy in Lung Cancer Cells: A Brief Overview - Chiaviello, Angela (Molecular Diversity Preservation International (MDPI), 2011)
Lung cancer remains one of the most common cancer-related causes of death. This type of cancer typically develops over a period of many years, and if detected at an early enough stage can be eliminated by a variety of treatments including photodynamic therapy (PDT). A critical discussion on the clinical applications of PDT in lung cancer is well outside the scope of the present report, which, in turn focuses on mechanistic and other aspects of the photodynamic action at a molecular and cellular level. The knowledge of these issues at pre-clinical levels is necessary to develop, check and adopt appropriate clinical protocols in the future. This report, besides providing general information, includes a brief overview of present experimental PDT and provides some non-exhaustive information on current strategies aimed at further improving the efficacy, especially in regard to lung cancer cells.